Afghanistan Poverty Status Update : An Analysis Based on National Risk and Vulnerability Assessment 2007/08 and 2011/12 - World Bank (Washington, DC, 2015)
Afghanistan’s per capita Gross Domestic Product (GDP) grew at an average annual rate of 6.9 percent during that period. In contrast, in 2007-08, 36 percent of Afghans were poor, and four years later, still, more than one in three Afghans did not have the buying power to satisfy their basic food and non-food needs. Economic growth in Afghanistan, therefore, is not in and of itself enough to reduce poverty. To achieve poverty reduction, economic growth needs to be far more inclusive for everyone, regardless of their circumstances. While economic growth is necessary to reduce poverty, the poor must actually benefit from that growth. Poverty reduction hinges on the ability of the poorest to earn a good living; accumulate, control, and protect assets; and access quality services and opportunities. For Afghanistan, this means: strengthening agriculture, investing in human development, managing and mitigating risk.